The influence of brand image, social media marketing and price on the decision to purchase Converse shoes - Anjani, Ni Ketut; Yasa, I Putu Eka Sutasoma Sedana (EDUCTUM: Journal Research, 2026)
The research was conducted with the aim of knowing about price, social media marketing, and brand branding, influencing consumer actions in the purchasing process. The sample in this study was customers of several official Converse outlets spread across various large shopping centers in Bali, such as Beachwalk Shopping Center, Discovery Shopping Mall, ICON Mall Bali, Ramayana Dauh Puri, and Living World Denpasar as many as 150 people. The data analysis technique used PLS 4. From the results of the study, it was obtained that marketing on social media had a large and positive influence on all buyer decisions, just as branding had a positive influence and significantly influenced prices and greatly influenced consumer decisions about what to buy. The suggestion that can be given by researchers is that the Converse Company is expected to continue to innovate in product design, create more interesting content, evaluate pricing policies, and continuously carry out promotions.